Analisis Permintaan Penyaluran Gas PT PGN Dengan Metode Time Series - Mardila Nur Imamah; Hafid Syaifullah (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
In the case of gas transmission, the calculation of the gas delivered and the gas currently in the pipe is of course required to be a safe amount in the sense of neither less nor more. A condition where the amount of gas is less than the minimum value of the pipe capacity can cause damage to the pipe because the pressure is below the normal point. Meanwhile, conditions where the gas in the pipe exceeds the maximum capacity value is also very dangerous because it can cause accidents such as pipe leaks and explosions. Therefore, this research was carried out to determine the value of forecasting gas demand by PT PGN to be able to find out the range of gas volumes that must be stored and then distributed by Pertamina Gas to meet PT PGN's demand. Forecasting is a technique of predicting the influence of prevailing conditions and situations on future developments. The method generally used in forecasting is the quantitative method using the time series method.